New insights involving the home team advantage - Swartz, T. B.; Arce, A. (International Journal of Sports Science and Coaching, 2014)
Although the home team advantage is known to exist in many sports, there are nuances of the advantage that are less well understood. In this paper, we investigate various aspects of the home team advantage including changes in the advantage over time, the relationship of the advantage to the overall scoring rate and differential advantages within leagues. The analysis is mainly based on descriptive statistics and is confined to the home team advantage pertaining to the National Hockey League and the National Basketball Association.